Parental obligations, care and HIV treatment: How care for others motivates self-care in Zimbabwe. (November 2020) - Skovdal, Morten; Maswera, Rufurwokuda; Kadzura, Noah; Nyamukapa, Constance; Rhead, Rebecca; Wringe, Alison; Gregson, Simon
This article examines how parental obligations of care intersect with HIV treatment-seeking behaviours and retention. It draws on qualitative data from eastern Zimbabwe, produced from 65 interviews. Drawing on theories of practice and care ethics, our analysis revealed that norms of parental obligation and care acted as key motivators for ongoing engagement with HIV services and treatment. Parents' attentiveness to the future needs of their children ( caring about ), and sense of obligation ( taking care of ) and improved ability to care ( caregiving ) following treatment initiation, emerged as central to understanding their drive for self-care and engagement with HIV services.